2012
DOI: 10.1002/qj.1948
|View full text |Cite
|
Sign up to set email alerts
|

Surface pressure record of Tibetan Plateau warming since the 1870s

Abstract: The Tibetan Plateau (TP) is the world's highest and largest plateau. By acting as an elevated thermal source as well as a topographic barrier, the TP has a profound impact on both local weather and global climate. The TP has recently been warming at a faster rate than the entire Northern Hemisphere. However, the lack of instrumental records prior to the 1950s limits our ability to place this recent warming in a longer-term context. Here we show that over the plateau, because of its high elevation, the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…There is, however, evidence that large-scale meteorological processes such as El Niño can impact the weather on Mount Everest [10], thereby impacting the hypoxic and hypothermic stresses. Long-term trends arising from global warming can also impact these stresses through changes in the background meteorological fields [10,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…There is, however, evidence that large-scale meteorological processes such as El Niño can impact the weather on Mount Everest [10], thereby impacting the hypoxic and hypothermic stresses. Long-term trends arising from global warming can also impact these stresses through changes in the background meteorological fields [10,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…This leads to a reduction in the degrees of freedom associated with a particular time series that can have an impact on the significance of trends and correlations38. To take this into account, the statistical significance of the trends and correlations were assessed using a Monte-Carlo approach that generated 10,000 synthetic time series that share the same spectral characteristic as that of the underlying time series, thereby capturing any temporal autocorrelation3940. The distribution of trends and/or correlations from the set of synthetic time series was then used to estimate the statistical significance of the actual result.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, TP is one of the regions most sensitive to climate change (Liu and Chen 2000, Wu et al 2007. Recent investigations have revealed that desertification has become a severe environmental problem in the TP (Tu et al 1999, Feng et al 2006, Xue et al 2009, Dong et al 2010 due to the significant warming (Liu and Chen 2000, Wu et al 2007, Solomon et al 2007, Wang et al 2008, Krause et al 2010, Moore 2012. If desertification greatly expands, it may have unforeseen influence on the global climate given the important role of the TP as an elevated heat source and sink that drive global circulation (Fang et al 2004.…”
Section: Introductionmentioning
confidence: 99%